Migration of phthalates from plastic containers into soft drinks and mineral water - Bošnir, Jasna (Array, 2007)
Summary: The aim of this study was to determine the level of phthalate migration from plastic containers to soft drinks and mineral water and to identify a possible relationship between the amount and type of phthalate migration, type of preservative used, and the pH of the sample.